Religious Moderation in Christian School at East Nusa Tenggara - Risambessy, Johanis; Lado, Ivana Enjela Lay; Loes, Juliana (Proceeding International Conference on Religion, Science and Education, 2025)
The study aimed to determine religious moderation in Christian Schools at East Nusa Tenggara. The applied religious moderation is measured based on four indicators, national commitment, tolerance, non-violence, and accommodation of local culture. This study used a quantitative study with a descriptive approach. The population in this study was 73 teachers, with the sample used being a saturated sample. Data were collected using a questionnaire, comprising 17 items related to the implementation of religious moderation. Before the instrument was used, its validity and reliability were tested first. After that, the data were analyzed using descriptive quantitative analysis. The results of the study showed a religious moderation in Christian Schools at East Nusa Tenggara by teachers was proven to be very good with an average of 88 percent, with details of the national commitment indicator of 90 percent, the tolerance indicator of 91 percent, the non-violence indicator of 92 percent, and the accommodation for local culture of 78 percent. The recommendation in this study is school can make the religious moderation program a role model for another Christian schools. Local education departments can also create standards related to the implementation of religious moderation to be applied in Christian schools.